Preparation method and application of pyrenyl metal organic framework two-dimensional ultrathin nanosheet

The pyrene-based metal organic frame two-dimensional ultra-thin nanosheets were directly synthesized by a solvent-thermal method without regulator control, which solved the problems of large size, ultra-thin thickness, complete exposure of active sites and low yields in the prior art, and significantly improved the photocatalytic water decomposition hydrogen production performance of nanosheets.

CN119591894AActive Publication Date: 2025-03-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411781757.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

It is difficult to prepare two-dimensional ultra-thin MOF nanosheets with large size, ultra-thin thickness, fully exposed active sites and low yields, and the prepared nanosheets have low photocatalytic efficiency.

Method used

Through a solvent-thermal method without regulator control, pyrene-based metal organic frame two-dimensional ultrathin nanosheets were directly synthesized, and nanosheets with micron sizes were prepared using 1,3,6,8-tetracarboxybenzene (4-carboxybenzene)pyrene (H4TBAPy) ligand and metal salt in an organic solvent to prepare nanosheets with a thickness of less than 3 nm and micrometers.

Benefits of technology

High yield preparation without surfactant is achieved, the photocatalytic water decomposition hydrogen production performance of nanosheets is significantly improved, the carrier transfer path is shortened, and the specific surface area exposure is larger.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591894A_ABST
    Figure CN119591894A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a pyrenyl metal organic framework two-dimensional ultrathin nanosheet, and belongs to the technical field of catalytic materials. The preparation method comprises the following steps: respectively dispersing a 1, 3, 6, 8-tetra (4-carboxybenzene) pyrene ligand and a metal salt in an organic solvent or a mixed solution of the organic solvent and deionized water, uniformly stirring, dropwise adding the obtained ligand solution into a metal salt solution in a stirring state, uniformly stirring, washing, and drying to obtain the 1, 3, 6, 8-tetra (4-carboxybenzene) pyrene complex. And filling the obtained mixed solution into a stainless steel reaction kettle containing a polytetrafluoroethylene lining, carrying out solvent heat treatment, cooling, centrifuging, washing, and freeze-drying to obtain a series of pyrenyl MOF two-dimensional ultrathin nanosheets. The method does not need a regulator, the preparation process is mild and simple, and the method has high repeatability and universality. The thickness of the prepared ultrathin two-dimensional MOF nanosheet is less than 3nm, and the ultrathin two-dimensional MOF nanosheet has the characteristics of micron size and large specific surface area, and can be used as an excellent candidate of a photocatalyst for producing hydrogen by photocatalytic decomposition of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and specifically relates to a preparation method and application of a pyrene-based metal organic framework two-dimensional ultra-thin nanosheet. Background Art

[0002] Compared with bulk or single crystal materials, two-dimensional materials with large size, atomic or molecular thickness and high aspect ratio have unique physical and chemical properties. Two-dimensional nanomaterials occupy an important position in application fields such as separation, optoelectronics, and catalysis. In recent years, two-dimensional (2D) metal organic framework (MOF) nanosheets, as new members of the two-dimensional family, have attracted great attention due to their tunable structure and function, large specific surface area and ultra-large porosity, and related research has developed rapidly in the fields of chemistry and materials. Compared with 3D bulk MOF crystals, 2D ultrathin MOF nanosheets have high catalytic active sites and large surface area, which are conducive to ensuring rapid mass transfer and high catalytic activity. These characteristics give 2D ultrathin MOF nanosheets great application potential in catalysis, energy storage, and electronic sensors.

[0003] In recent years, methods for preparing two-dimensional nanosheets have been synthesized and developed, including top-down and bottom-up methods. The top-down method is to ultrasonically exfoliate the layered bulk MOF to obtain nanosheets. However, the nanosheets obtained by this method usually face the disadvantages of morphological destruction, restacking, low yield, and this method is only suitable for MOFs with weak interlayer interactions. Bottom-up methods for directly synthesizing MOF nanosheets, such as surfactant-assisted synthesis and interface-assisted synthesis strategies, are preferred methods for preparing MOF nanosheets with high yield and good dispersion. However, low yield, the difficulty in completely removing the introduced surfactant, resulting in the masking of catalytic active sites, and other problems affect the photocatalytic process. Therefore, there is an urgent need for a method for directly synthesizing large-sized, surfactant-free, universal, and large-scale ultrathin 2D MOF nanosheets. Summary of the invention

[0004] The purpose of the present invention is to propose a preparation method and application of a pyrene-based metal organic framework two-dimensional ultra-thin nanosheet, so as to solve the problems existing in the current preparation process of nanosheets, such as it is difficult to achieve large size, ultra-thin thickness, complete exposure of active sites, low yield, and low photocatalytic efficiency of the prepared nanosheets; the 2D ultra-thin MOF nanosheets prepared by the present invention have the characteristics of micron size and surface-free surfactant, which can effectively shorten the transfer distance of carriers from the bulk phase to the surface, while exposing a larger specific surface area, significantly improving the performance of photocatalytic water decomposition to produce hydrogen.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a pyrene-based metal organic framework two-dimensional ultrathin nanosheet, comprising the following steps:

[0007] (1) dispersing 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) ligand and metal salt in an organic solvent or a mixed solution of an organic solvent and deionized water, respectively, and stirring uniformly;

[0008] (2) adding the ligand solution obtained in step (1) dropwise to the metal salt solution under stirring and stirring evenly;

[0009] (3) The mixed solution obtained in step (2) is placed in a stainless steel reactor lined with polytetrafluoroethylene, reacted at 100-140° C. for 3-24 hours, centrifuged after cooling, washed, and freeze-dried to obtain a two-dimensional ultrathin nanosheet powder.

[0010] Based on the above technical solution, further, the metal salt described in step (1) includes chlorides, nitrates, sulfates, acetates and hydrates of Mn, Co, Cd and Ni.

[0011] Based on the above technical solution, further, the metal salt described in step (1) includes MnCl4, Co(NO3)2, Cd(NO3)2, NiCl2 and hydrates thereof.

[0012] Based on the above technical solution, further, the molar ratio of the metal atom of the metal salt to the 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene(H4TBAPy) ligand in step (1) is 5:1 to 1:1, and the concentration of the 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene(H4TBAPy) ligand is 0.1 to 10 mmol L -1 The concentration of metal salt is 0.1~20mmol L -1 .

[0013] Based on the above technical solution, further, the organic solvent described in step (1) includes N,N-dimethylformamide and N,N-diethylformamide, and the volume ratio of the organic solvent to water in the mixed solution is 64:1 to 16:1.

[0014] Based on the above technical solution, further, the stirring time in step (1) and step (2) is 20 to 40 minutes.

[0015] Based on the above technical solution, further, in step (3), the reaction temperature is 110°C to 130°C, and the reaction time is 3h to 8h.

[0016] Based on the above technical scheme, further, the centrifugal speed described in step (3) is 5000-8000 r / min, the centrifugal time is 2-3 min, the solvents used for washing are N,N-dimethylformamide and acetonitrile, N,N-dimethylformamide is washed 1-4 times, acetonitrile is washed 1-4 times, and freeze-drying is specifically liquid nitrogen freeze-drying.

[0017] In a second aspect, the present invention provides a pyrene-based metal organic framework two-dimensional ultrathin nanosheet prepared by the above preparation method.

[0018] Based on the above technical solution, further, the thickness of the pyrene-based metal organic framework two-dimensional ultra-thin nanosheet is 1 to 3 nm, and the size is 1 to 6 μm.

[0019] In a third aspect, the present invention provides the use of the above-mentioned pyrene-based metal organic framework two-dimensional ultrathin nanosheets in photocatalytic water decomposition to produce hydrogen.

[0020] Based on the above technical scheme, further, the application is specifically as follows: adding the pyrene-based metal organic framework two-dimensional ultrathin nanosheets to a mixed solution of acetonitrile, water and ascorbic acid, adding H2PtCl6 aqueous solution, transferring into a sealed reactor, evacuating, photodepositing the co-catalyst Pt, the light source is a 100-500W xenon lamp (λ≥420nm), and then photocatalytic water decomposition to produce hydrogen.

[0021] Based on the above technical solution, further, the addition amount of the pyrene-based metal organic framework two-dimensional ultrathin nanosheet is 10-30 mg, and the mixed solution for photocatalytic water decomposition to produce hydrogen consists of 1000-2000 μL water, 50-150 mL MeCN and 25-45 mg ascorbic acid.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention directly synthesizes a series of pyrene-based MOF two-dimensional ultrathin nanosheets through a solvent-thermal method without regulator control. The method does not require a regulator, has mild conditions, a simple preparation process, high repeatability, and strong universality. The synthesized ultrathin two-dimensional MOF nanosheets are less than 3nm thick and have a micron size.

[0024] 2. The method used in the present invention does not require the addition of surfactants to avoid masking the exposed active sites.

[0025] 3. The ultrathin 2D MOF nanosheets prepared by the present invention can effectively shorten the transfer distance of carriers from the bulk phase to the surface, and significantly improve the performance of photocatalytic water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1These are the SEM image (a), TEM image (b), AFM image (c) and XRD image (d) of the Mn-TBAPy-UTNS two-dimensional ultrathin nanosheets prepared in Example 1.

[0027] Figure 2 These are the SEM image (a), AFM image (b) and XRD image (c) of Co-TBAPy-UTNS prepared in Example 2.

[0028] Figure 3 These are the SEM image (a), AFM image (b) and XRD image (c) of the Cd-TBAPy-UTNS prepared in Example 3.

[0029] Figure 4 These are the SEM image (a), AFM image (b) and XRD image (c) of the Ni-TBAPy-UTNS prepared in Example 4.

[0030] Figure 5 It is the activity of the photocatalytic water decomposition and hydrogen production reaction of the Mn-TBAPy-UTNS two-dimensional ultrathin nanosheets in Example 6, wherein a is the hydrogen production rate result graph of the ultrathin two-dimensional nanosheets and the bulk sample, and b is the hydrogen production time curve result graph of the Mn-TBAPy-UTNS two-dimensional ultrathin nanosheets.

[0031] Figure 6 These are the electrochemical impedance spectra (a) and fluorescence spectra (b) of the Mn-TBAPy-UTNS two-dimensional ultrathin nanosheets tested in Example 7 and Example 8. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to examples and drawings, but the embodiments of the present invention are not limited thereto.

[0033] Example 1

[0034] This embodiment provides a method for preparing Mn-TBAPy-UTNS two-dimensional ultrathin nanosheets, which specifically includes the following steps:

[0035] 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene H4TBAPy ligand (5 mg) and MnCl4·4H2O (2.3 mg) were placed in two 25 mL beakers respectively, and DMF (8 mL) was added respectively, followed by stirring for 30 min, and then the ligand solution was added dropwise to the metal salt solution and continued to stir for 30 min; the above solution was poured into a stainless steel reactor containing 25 mL polytetrafluoroethylene lining, and then transferred to a programmable temperature-controlled oven, heated to 120°C and kept warm for 6 h, naturally cooled to room temperature, centrifuged, washed with DMF and acetonitrile respectively, and freeze-dried to obtain a fluffy yellow powder product named Mn-TBAPy-UTNS.

[0036] Figure 1 a shows the SEM image of the Mn-TBAPy-UTNS prepared in this example. The nanosheets are micrometer-sized and have ultrathin thickness. Figure 1 b is the TEM image of Mn-TBAPy-UTNS. Figure 1 c is the AFM image of Mn-TBAPy-UTNS, showing that the thickness of the nanosheet is about 2.1 nm; Figure 1 d is the comparison diagram of XRD and single crystal of Mn-TBAPy-UTNS (SCIENCE CHINAChemistry, 2020, 63(12), 1756-1760.), which proves the successful preparation of nanosheets.

[0037] Example 2

[0038] This embodiment provides a method for preparing Co-TBAPy-UTNS two-dimensional ultrathin nanosheets, which specifically includes the following steps:

[0039] 1,3,6,8-Tetrakis(4-carboxyphenyl)pyrene H4TBAPy ligand (10 mg) and Co(NO3)2·6H2O (5.5 mg) were placed in two 25 mL beakers respectively, and DEF (7.75 mL) and water (0.25 mL) were added respectively, and then stirred for 30 min; then the ligand solution was added dropwise to the metal salt solution and stirring was continued for 30 min; the above solution was poured into a stainless steel reactor containing 25 mL polytetrafluoroethylene lining, and then transferred to a programmable temperature controlled oven, heated to 120°C and kept warm for 6 h, naturally cooled to room temperature, centrifuged, washed with DMF and acetonitrile respectively, and freeze-dried to obtain a fluffy yellow powder of the product, which was named Co-TBAPy-UTNS.

[0040] Figure 2 a shows the SEM image of Co-TBAPy-UTNS prepared in this example. The nanosheets are micrometer-sized and have ultrathin thickness. Figure 2 b shows the AFM image of Mn-TBAPy-UTNS, indicating that the thickness of the nanosheets is about 1.7 nm; Figure 1 c is a comparison diagram of XRD and single crystal of Co-TBAPy-UTNS (Journal of Solid State Chemistry, 285, 121252.), which proves the successful preparation of nanosheets.

[0041] Example 3

[0042] This embodiment provides a method for preparing Cd-TBAPy-UTNS two-dimensional ultrathin nanosheets, which specifically includes the following steps:

[0043] 1,3,6,8-Tetrakis(4-carboxyphenyl)pyrene H4TBAPy ligand (3.4 mg) and Cd(NO3)2·4H2O (4.6 mg) were placed in two 25 mL beakers, and DMF (8 mL) and H2O (0.5 mL) were added respectively, and then stirred for 30 min; next, the ligand solution was added dropwise to the metal salt solution and stirred for another 30 min; the above solution was poured into a stainless steel reactor containing 25 mL polytetrafluoroethylene lining, and then transferred to a programmable temperature-controlled oven, heated to 120°C and kept warm for 6 h, naturally cooled to room temperature, centrifuged, washed with DMF and acetonitrile respectively, and freeze-dried to obtain a fluffy yellow powder of the product, which was named Cd-TBAPy-UTNS.

[0044] Figure 3 a shows the SEM image of Cd-TBAPy-UTNS prepared in this example. The nanosheets are micrometer-sized and have ultra-thin thickness. Figure 2 b is the AFM image of Cd-TBAPy-UTNS, showing that the thickness of the nanosheet is about 1.5 nm; Figure 1 c is a comparison chart of XRD and single crystal of Cd-TBAPy-UTNS (Advanced Materials, 2018, 30, 1803401), which shows the successful preparation of nanosheets.

[0045] Example 4

[0046] This embodiment provides a method for preparing Ni-TBAPy-UTNS two-dimensional ultrathin nanosheets, which specifically includes the following steps:

[0047] 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene H4TBAPy ligand (10 mg) and NiCl2·6H2O (2.6 mg) were placed in two 25 mL beakers, and a mixed solvent of DMF (7.5 mL) and water (0.5 mL) was added respectively, and then stirred for 30 min; next, the ligand solution was added dropwise to the metal salt solution, and stirring was continued for 30 min; the above solution was poured into a stainless steel reactor containing 25 mL polytetrafluoroethylene lining, and then transferred to a programmable temperature-controlled oven, heated to 120°C and kept warm for 6 h, naturally cooled to room temperature, centrifuged, washed with DMF and acetonitrile respectively, and freeze-dried to obtain a fluffy yellow powder of the product, which was named Ni-TBAPy-NS.

[0048] Figure 4 a shows the SEM image of Ni-TBAPy-UTNS prepared in this example. The nanosheets are micrometer-sized and have ultra-thin thickness. Figure 4 b is the AFM image of Ni-TBAPy-UTNS, showing that the thickness of the nanosheet is about 1.2 nm; Figure 4c is a comparison chart of XRD and single crystal of Ni-TBAPy-UTNS (Journal of the American Chemical Society, 2022, 144(6), 2747-2754.), proving the successful preparation of nanosheets.

[0049] Example 5

[0050] This example provides the deposition of the Mn-TBAPy-UTNS and Mn-TBAPy-SC (SCIENCE CHINA Chemistry, 2020, 63 (12), 1756-1760.) co-catalysts prepared in Example 1, which specifically includes the following steps:

[0051] Weigh 20 mg of sample and place it in a reactor containing 1500 μL of water, 100 mL of acetonitrile and 35 mg of ascorbic acid (AA) as the same solvent as the photocatalytic reaction. Add 60 μL of 1 mg mL -1 Chloroplatinic acid (H2PtCl6) aqueous solution was prepared, the reactor was sealed and evacuated, and the reaction mixture was deposited for 1 h under full spectrum irradiation with a 300W xenon lamp as the light source to obtain Pt-loaded Mn-TBAPy nanosheets (denoted as: “Pt / Mn-TBAPy-UTNS and Pt / Mn-TBAPy-SC”).

[0052] Example 6

[0053] This example provides an experiment of photolysis of water to generate hydrogen by Mn-TBAPy-SC single crystal and Mn-TBAPy-UTNS ultrathin nanosheets: 20 mg of catalyst powder (Mn-TBAPy-UTNS and Mn-TBAPy-SC) was dispersed in a mixed solution of 1500 μL of water, 100 mL of acetonitrile and 35 mg of ascorbic acid (AA), and 1 mg mL of AA was added to the mixture. -1 of H2PtCl6 aqueous solution. The reaction solution is then transferred to a 400mL Pyrex reactor, and the reactor is sealed. At the same time, the circulating cooling device is turned on to ensure that the temperature of the reaction system is at 15°C, and the vacuum pump is connected for 15 minutes to ensure that the air in the reactor is completely removed. The same operation as in Example 5 is performed, first photodepositing a Pt co-catalyst with a mass percentage of 0.3%, and then conducting a photocatalytic water decomposition experiment test. Top irradiation is adopted, and a 300W xenon lamp (λ≥420nm) is used as the light source. Samples are taken every 1h, and the amount of hydrogen produced is detected by gas chromatography.

[0054] The results are as follows Figure 5 As shown, from Figure 5It can be seen that the rate of photocatalytic water decomposition and hydrogen production by Pt / Mn-TBAPy-UTNS is one order of magnitude higher than that of single crystal Pt / Mn-TBAPy-SC.

[0055] Example 7

[0056] This example provides the electrochemical impedance spectroscopy (EIS) test of Mn-TBAPy-UTNS and Mn-TBAPy-SC: 5 mg of Mn-TBAPy-UTNS powder and Mn-TBAPy-SC were respectively weighed and ultrasonically dispersed in 0.5 mL of anhydrous methanol solution containing 0.05% nafin. Then 10 μL of the dispersed suspension was dropped on a 0.25 cm 2 FTO, and dried naturally. -1 EIS was tested in sodium sulfate solution. The reference electrode was Ag / AgCl electrode and the counter electrode was a platinum electrode. The EIS test process potential was 0.6V vs RHE and the frequency was 0.1~1000HZ.

[0057] Figure 6 a shows the experimental results of EIS, indicating that Mn-TBAPy-UTNS has smaller charge transfer resistance and better charge separation ability than Mn-TBAPy-SC.

[0058] Example 8

[0059] Fluorescence spectrum (PL) test: Powder samples (Mn-TBAPy-UTNS and Mn-TBAPy-SC) were used for testing, and the excitation wavelength used was 375 nm.

[0060] Figure 6 b shows the fluorescence spectroscopy (PL) experimental results of Mn-TBAPy-UTNS and Mn-TBAPy-SC, indicating that Mn-TBAPy-SC has stronger fluorescence intensity than Mn-TBAPy-UTNS.

Claims

1. A method for preparing a pyrene-based metal organic framework two-dimensional ultrathin nanosheet, characterized in that: The steps include: (1) dispersing 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) ligand and metal salt in an organic solvent or a mixed solution of an organic solvent and deionized water, respectively, and stirring uniformly; (2) adding the ligand solution obtained in step (1) dropwise to the metal salt solution under stirring and stirring evenly; (3) The mixed solution obtained in step (2) is placed in a stainless steel reactor lined with polytetrafluoroethylene, reacted at 100-140° C. for 3-24 hours, centrifuged after cooling, washed, and freeze-dried to obtain a two-dimensional ultrathin nanosheet powder.

2. The preparation method according to claim 1, characterized in that: The metal salt described in step (1) includes chlorides, nitrates, sulfates, acetates and hydrates of Mn, Co, Cd and Ni; the molar ratio of the metal atom of the metal salt to the 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) ligand is 5:1 to 1:1, and the concentration of the 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) ligand is 0.1 to 10 mmol L -1 The concentration of metal salt is 0.1~20mmol L -1 .

3. The preparation method according to claim 1, characterized in that: The organic solvent described in step (1) includes N, N-dimethylformamide and N, N-diethylformamide, and the volume ratio of the organic solvent to water in the mixed solution is 64:1 to 16:

1.

4. The preparation method according to claim 1, characterized in that: The stirring time in step (1) and step (2) is 20 to 40 minutes.

5. The preparation method according to claim 1, characterized in that: In step (3), the reaction temperature is 110° C. to 130° C., and the reaction time is 3 h to 8 h.

6. The preparation method according to claim 1, characterized in that: The centrifugal speed described in step (3) is 5000-8000 r / min, the centrifugal time is 2-3 min, the solvents used for washing are N,N-dimethylformamide and acetonitrile, N,N-dimethylformamide washing is 1-4 times, acetonitrile washing is 1-4 times, and freeze drying is specifically liquid nitrogen freeze drying.

7. A pyrene-based metal organic framework two-dimensional ultrathin nanosheet obtained by the preparation method according to any one of claims 1 to 6.

8. The pyrene-based metal organic framework two-dimensional ultrathin nanosheet according to claim 7, characterized in that: The pyrene-based metal organic framework two-dimensional ultra-thin nanosheet has a thickness of 1 to 3 nm and a size of 1 to 6 μm.

9. Use of the pyrene-based metal organic framework two-dimensional ultrathin nanosheets according to claim 7 or 8 in photocatalytic water decomposition to produce hydrogen.

Citation Information

Patent Citations

  • Metal organic framework Mn-MOF single-crystal material, nanosheet, preparation and application

    CN112442186A

  • Preparation and application of Tb-MOF nanosheets based on pyrene tetracarboxylic acid

    CN113413917A

  • Preparation method and application of P-type pyrenyl metal organic framework single crystal material and nanobelt

    CN114130431A

Cited By

  • Kilogram-level preparation method of metal organic thin-layer material

    CN120966037A